Contributions to the knowledge of Torrenticolid water mites (Acari: Hydrachnidia) in Doupengshan, China - Gu, Xinyao; Jin, Daochao; Yi, Tianci; Guo, Jianjun (Zootaxa, 2019)
Six species of Torrenticolidae Piersig, 1902 (Acari: Hydrachnidia) from Doupengshan are presented, including four species of the genus Torrenticola Piersig, 1896 (T. trigona Gu & Guo, sp. nov., T. siamis Pešić & Smit, 2009, T. tenuichelicera Gu & Guo, 2018 and T. tetraporella Cook, 1967), and two species of the genus Monatractides K. Viets, 1926 (M. hamatapodemus Gu & Guo, sp. nov. and M. oxystoma (Viets, 1935)), of which T. siamis is recorded for the Chinese fauna for the first time. Detailed descriptions for the new and newly recorded species and a key to all species of Torrenticolidae so far known from China are provided. Furthermore, the first description is given for the female of T. tenuichelicera.